2022
DOI: 10.1155/2022/8174310
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Multislice Spiral CT and Three-Dimensional Image Reconstruction Technology in the Observation of Ankle Sports Injury under the Microscope

Abstract: In order to solve the problem of multislice spiral CT and three-dimensional image reconstruction technology in the observation of ankle sports injuries under the microscope, to meet the needs of the accuracy of the diagnosis of traumatic fractures, to make up for the shortcomings of the traditional treatment cycle, and to improve the recovery speed of patients. The subjects were inpatients in the Orthopedics and Traumatology Department of a hospital from January 2020 to January 2021.The ankle joint belongs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…CT is more sensitive in fracture detection than X-ray, US, stress radiography, and clinical diagnostics. Studies have confirmed that spiral CT and 3D imaging reconstruction technology have high uniqueness and sensitivity for the diagnosis of joint and ligament injuries, with an area under the curve of 0.954, which can make up for the shortage of X-rays in further assessment of ATFL acute injuries and soft tissues, with faster scanning speed and better patient coordination[ 32 ].…”
Section: Imaging Evaluationmentioning
confidence: 99%
“…CT is more sensitive in fracture detection than X-ray, US, stress radiography, and clinical diagnostics. Studies have confirmed that spiral CT and 3D imaging reconstruction technology have high uniqueness and sensitivity for the diagnosis of joint and ligament injuries, with an area under the curve of 0.954, which can make up for the shortage of X-rays in further assessment of ATFL acute injuries and soft tissues, with faster scanning speed and better patient coordination[ 32 ].…”
Section: Imaging Evaluationmentioning
confidence: 99%
“…Multi-slice spiral CT is a new generation of CT products introduced at the North American Radiology Annual Meeting in 1998. It is an imaging system with a multi-row wide-body detector structure and a single exposure of the bulb tube to obtain multi-layer image data, representing the highest level and development direction of today's clinical CT machines [7]. Compared with traditional CT, multi-slice spiral CT obtains three-dimensional image information and has the following advantages.…”
Section: Features Of Multi-slice Spiral Ctmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%